Guided Imagery in Group Counseling to Reduce Excessive Self-Awareness Emotions: Guided Imagery dalam Konseling Kelompok untuk Mengurangi Emosi Kesadaran Diri Berlebihan - Nurfaridah, Kharisma; Hasibuan, Ali Daud (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Adolescents often experience intense self-conscious emotions such as shame, guilt, and anxiety, which may hinder their confidence and social interaction. Background (Specific): At Madrasah Aliyah Muallimin UNIVA Medan, many students were found to struggle with excessive self-conscious emotions, leading to avoidance behaviors and decreased academic engagement. Knowledge Gap: While guided imagery has been studied in reducing anxiety and stress, its specific effect on overly self-conscious emotions among Islamic high school students remains underexplored. Aim: This study investigates the effectiveness of group counseling with guided imagery in reducing excessive self-conscious emotions in MA students. Results: Using a quasi-experimental pretest-posttest control design with 16 purposively sampled students, findings revealed a significant reduction in self-conscious emotions in the experimental group (M pretest = 60.38; M posttest = 56.00; p < 0.05), supported by paired sample t-test results. Novelty: The study is among the first to apply guided imagery in group counseling within an Islamic educational setting, focusing specifically on excessive self-conscious emotions. Implications: The results highlight guided imagery as a practical and culturally adaptable intervention for school counseling, with potential to enhance students’ self-confidence, emotional regulation, and overall academic performance.Highlight : Group counseling with guided imagery effectively reduces excessive self-conscious emotions. Students gain relaxation and positive emotional control through visualization. The method improves confidence and supports emotional well-being Keywords : Counseling, Guided Imagery, Overly Self-Conscious Emotions, Group Counseling, Students